Ecological-trophic structure of soil microbial communities in the the middle Ob floodplain - Ellina G. Nikitkina; Inna V. Lushchaeva; Victor A. Nikitkin; Sergey N. Kirpotin; Larisa G. Kolesnichenko (Acta Biologica Sibirica)
Soil microbiota plays an integral role in biogeochemical cycles, being used as a key metric of changes and a means of integrated characterization of processes. The paper presents the results of microbiological analysis of soils from the central part of the middle Ob floodplain. The ecological and trophic structure of soil microbial communities was investigated to identify the leading physiological groups of heterotrophic bacteria involved in biogeochemical transformation of organic matter in soil. The relationship of bacteria of different physiological groups with seasonal variations and physical and chemical properties of soils, and the links between bacteria were identified and evaluated. The data obtained can be used to evaluate climate-regulating functions of microbial communities in floodplain soils and assess the potential of the middle Ob floodplain in terms of environmental services and nature management.